FTO diversely influences sensitivity of neuroblastoma cells to various chemotherapeutic drugs - Lin, Meizhen; Hua, Zhongyan; Li, Zhijie (Frontiers in Pharmacology, 2024)
Chemotherapy resistance is a significant factor in treatment failure in patients with neuroblastoma (NB), and directly affect patient prognosis. Therefore, identifying novel therapeutic targets to enhance chemosensitivity is essential to improve the cure rate and prognosis of patients with NB. In this study, we investigated the role of FTO in chemosensitivity of NB cells to various chemotherapeutic drugs. Our results showed that high FTO expression was positively correlated with increased survival probability and favorable prognostic factors in patients with NB. FTO overexpression inhibited cell proliferation, whereas FTO knockdown promoted cell proliferation in NB cells. FTO expression alteration had contrasting effects on NB cells sensitivity to etoposide but had no significant impact on sensitivity to cisplatin. Downregulation of FTO reduced the sensitivity of NB cells to paclitaxel, whereas upregulation of FTO enhanced its sensitivity. Additionally, the sensitivities between patients with lower and higher FTO expression to various chemotherapeutic drugs or small-molecule inhibitors were different. Thus, FTO affects the sensitivities of NB cells differently depending on the different chemotherapeutic drugs and small-molecule inhibitors. This finding may guide physicians and patients choose the appropriate chemotherapeutic drugs or smallmolecule inhibitors for treatment. Chemoresistance is a leading cause of treatment failure, highlighting the need to explore new therapeutic targets and strategies for patients with NB(Q. Li et al., 2023).The fat mass and obesity-associated (FTO) gene is a nuclear protein of the AlkB related non-haem iron and 2-oxoglutarate-dependent oxygenase superfamily, playing a role in regulating energy metabolism, fat formation, cell differentiation, neurodevelopment, and tumor progression. Particularly, it plays an important role in various types of cancers(Y.